LANGUAGE ATTITUDES AND INDONESIAN LANGUAGE LEARNING IN HIGHER EDUCATION: A RELEVANT STUDY - Sanulita, Henny; Judijanto, Loso; Prananda, Gingga; Fauzi, Muhammad Sukron; HD, Moh. Imam (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2024)
This research aims to explore language attitudes and Indonesian language learning in higher education. The design of this research is a literature review or literature review. A literature review is a description of theories, findings and other research materials obtained from reference materials as a basis for research activities. A literature review contains reviews, abstracts and the author's thoughts from various library sources (articles, books, slides, Internet information) about the topic in question. The Indonesian language course is one of the higher education courses designed to train students to acquire Indonesian language skills, especially academic writing and scientific presentations as a means of learning science. Indonesian is designed to improve students' ability to speak Indonesian fluently and accurately, because it can be an indicator of students' sense of nationalism as Indonesians. In addition, the course aims to cultivate students' skills in structuring and conveying ideas or concepts to facilitate ongoing dialogue and ensure efficient dissemination and management of knowledge